Mathematical foundations of advanced informatics: specifics of teaching the course with utilization of the system GRAN and utilization for participant-directed learning - Hrybiuk, Olena (Національний технічний університет "Харківський політехнічний інститут", 2021)
The article considers the issue of computer training of mathematics teachers in the context of using computer mathematics systems as a teaching tool. The analysis of propaedeutic tasks of the course “Mathematical foundations of Advanced Informatics” (MFAI) is carried out. The system of tasks is considered and situational tasks are analyzed with the use of rules-guidelines and methodical instructions for solving problems with the use of the GRAN system. An updated syllabus of the training course is offered taking into account modern requirements. The analysis of the logical-structural scheme of the training course “Mathematical foundations of Advanced Informatics” (MFAI) is considered. The main advantages of using the GRAN system are demonstrated. The results of the conducted pedagogical experiment using the computer mathematics system GRAN are offered. Criteria, indicators and methods of diagnosing the effectiveness of student learning are substantiated. The classification of problems is carried out and examples of didactic materials for teaching the course using computer mathematics systems GRAN are offered.

У дослідженні розглядається проблематика інформатичної підготовки вчителів математики в контексті використання систем комп'ютерної математики як засобу навчання. Здійснено аналіз пропедевтичних завдань курсу “Математичні основи інформатики”. Розглядається система задач і аналізуються ситуаційн і задачі з використанням правил-орієнтирів та методичних вказівок до розв’язування завдань з використанням системи GRAN. Пропонується оновлений силабус навчального курсу із врахуванням сучасних вимог. Розглядається аналіз логічно-структурної схеми навчального курсу “Математичні основи інформатики”. Демонструються основні переваги використання системи GRAN. Пропонуються результати проведеного педагогічного експерименту з використанням системи комп’ютерної математики GRAN. Обґрунтовуються критерії, показники та методи діагностики ефективності навчання студентів. Здійснено класифікацію задач і пропонуються приклади дидактичних матеріалів для навчання з використанням систем комп’ютерної математики GRAN.
Математичні основи інформатики: особливості навчання курсу з використання системи комп’ютерної математики GRAN
Keywords: system of dynamic mathematics; computer-oriented learning environments; комп'ютерно-орієнтована методична система навчання; математичне моделювання